A model to teach non-rival and excludable goods in undergraduate microeconomics. (January 2017) - Wood, Aaron D.
Graphical abstract: Highlights: A model to teach non-rival and excludable goods in undergraduate microeconomics is presented. The model teaches theory and regulation for non-rival and excludable goods. A numerical exercise is included for use in the classroom. Abstract: Non-rival and excludable goods, often referred to as artificially-scarce goods or club goods, are discussed in principles of microeconomics textbooks, but they are not given a rigorous graphical analysis. This paper presents a model for non-rival and excludable goods that aligns with the intuition conveyed in introductory microeconomics textbooks. The model enables students to develop a rigorous understanding of the theory of non-rival and excludable goods, and it includes an allocatively efficient outcome, a private outcome, and a second-best solution outcome to exhibit the relative prices, quantities, profits, and welfare results that emerge in different regulatory frameworks. A numerical exercise solidifies the concepts presented in the theoretical model.